Consumers’ green purchase intention to visit green hotels: A value-belief-norm theory perspective. - Wang, Cen-Peng; Zhang, Qi; Wong, Philip Pong Weng*; Wang, Lei (Frontiers Media, 2023)
The theory of planned behavior (TPB) has dominated the limited number of green hotel visitation studies; however, those studies’ findings are often inconclusive or even controversial. Thus, research needs to move beyond using the TPB to measure consumers’ intention and behavior, and to experiment with alternative theoretical frameworks to explain behavioral change. Valuebelief-norm theory of environmentalism (VBN) proposed that various facets of values can influence individuals’ beliefs, subsequently effecting their moral obligations, ultimately, their pro-environmental behaviors. Hence, this study aims to examine the relationship between value components (i.e., Biospheric, altruistic, collectivistic), beliefs (i.e., explicit and implicit attitude), norms (i.e., social and personal norm), and green purchase intention to visit green hotels.